(3GdGbJUGO GdLRGFQj aj ehGLgI CReI JgGhj CSYGQ GdWGbI (B2014s - (3VjGA eLjO(B, (3GdehShjs ((3GdLRGFQ(B:s (3cfhR GdMceI(B,s, 2014)
(3jMJhj gPG GdcJGH Ydi NeS aUhd, YdjfG HGdJfejI bHd cd TiA, CeG GdaUd GdKGfj cdefG Yf JQGLY CSYGQ GdfaW a (B2014(3, hcPdc GfYcGSGJ JQGLYgGYdI MLe GdJLGQI GdNGQLjI ddLRGFQ,HGdEVGaI Edi GdSHjd dJMbjb GdJfejI GdeSJOGeI aj GdLRGFQ dehGLgI GfgjGQ CSYGQ GdHJQhd(B.(3haj GdCNjQ gd JJMed GdMcheGJ eSDhdjI GdaTd aj JMbjb GdJfejI GdeSJOGeI aj GdLRGFQ?cdG(B.s
(3eQGLY U(B.69s
Keywords: (3GdCReGJ GdEbJUGOjIs; (3GdEbJUGO(B-(3GdLRGFQs; (3GdWGbI GdHJQhdjIs